The prospective status of women in israel following a clash between the feminist and religious revolutions in the Israeli army - Pershitz, Anat (Studia Europaea Gnesnensia, 2019)
In the past decade, the Israeli Army (IDF) has been undergoing simultane-ously two ‘social revolutions’: a ‘feminist revolution’ and a “religious revolution”. The two revolutions have different and conflicting ideologies causing a clash of values. Feminist values demand the integration of women in the army without gender separation, whereas religious principles require modesty and gender separation. At the moment, in practice, religious values which under-mine women’s equal opportunities in the army outweigh democratic values. If the secular women and men in Israeli society will not act to deprive the IDF of its unofficial and unauthorized role of balancing conflicting values in society, the status and roles of women in the army will be downgraded, directly im-pacting gender inequality in the employment market.